STUDI KUALITATIF TENTANG PENGARUH STRUKTUR KELUARGA TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA - Cynthia Petra Haumahu; Criezta Korlefura (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyse the influence of family structure on student motivation and academic achievement using a phenomenological qualitative approach. Data were collected through semi-structured interviews with 12 junior high school and high school students from intact families and broken homes. Data analysis was conducted using thematic analysis, through a process of coding, theme identification, and validation of results. The results show that family structure indirectly influences motivation and academic achievement through the quality of emotional relationships, social support, and student adaptation strategies. Students from intact families demonstrate stronger intrinsic motivation, while students from broken homes face emotional barriers but show high resilience through the support of teachers and the school environment. These findings emphasise the importance of an ecological approach and self-determination theory in understanding children's learning dynamics. The research recommendations emphasise the need for family-based school guidance interventions and psychosocial support across the education system